2020
DOI: 10.20944/preprints202011.0306.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Different Modulatory Effects of Four Methicillin‐Resistant <em>Staphylococcus aureus</em> Clones on MG-63 Osteoblast-Like Cells

Abstract: Staphylococcus aureus is a Gram-positive bacterium causing a range of mild to life-threatening infections including bone infections such as osteomyelitis. S. aureus is able to invade and persist within non-professional phagocytic cells such as osteoblasts. In the present study four different S. aureus strains, 2SA-ST239-III, 5SA-ST5-II, 10SA-ST228-I, and 14SA-ST22-IVh were tested for their ability to modulate cell viability in MG-63 osteoblast-like cells following a successful invasion and persistence. Methici… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…However, only TI2, and not LAC, displayed lower osteoblast cytotoxicity and intra-osteoclast proliferation. These findings coincide with previous work establishing that S. aureus clinical isolates differ in their virulence, pathogenicity, and toxicity, and that a lower cytotoxicity correlates with increased persistence in vivo (34,35). We found major differences in specific tissue tropism among isolates.…”
Section: Modeling Hematogenous Osteomyelitis Using Nrs384 and Lacsupporting
confidence: 92%
See 1 more Smart Citation
“…However, only TI2, and not LAC, displayed lower osteoblast cytotoxicity and intra-osteoclast proliferation. These findings coincide with previous work establishing that S. aureus clinical isolates differ in their virulence, pathogenicity, and toxicity, and that a lower cytotoxicity correlates with increased persistence in vivo (34,35). We found major differences in specific tissue tropism among isolates.…”
Section: Modeling Hematogenous Osteomyelitis Using Nrs384 and Lacsupporting
confidence: 92%
“…However, our knowledge of the clinical behavior of these isolates is limited to only one patient per isolate, so it is currently unclear how these findings translate to a broader population. Further work is needed to determine specific bacterial factors that may promote differences in infection incidence and tropism, as well as if the lower cytotoxicity of TI2 contributes to chronicity as seen with other isolates (34, 35). It will be interesting to see if the incidence of sequestra or periosteal reactions – characteristic changes of chronic osteomyelitis - increases over time past the 5 weeks we examined here.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in previously published works, we demonstrated that internalization, using MG-63 cells, is a pathophysiological pathway of some methicillin-resistant S. aureus (MRSA) which depends on the total number of cells infected and not on the number of bacterial cells that enter each osteoblast. Furthermore, even if our strains were not homogeneous in terms of genetic backgrounds and virulence factors, ST22-IVh and ST239-III S. aureus showed higher intracellular persistence in host cells, making them more prone to developing chronic and recurrent infections, and the different genetic background was also accompanied by a different modulation of inflammatory phenomena, metabolism and antioxidant machinery [ 64 , 65 ].…”
Section: Mg-63 Osteoblast-like Cell Line As An Effective In Vitro mentioning
confidence: 99%
“…In this way, S. aureus induces inflammatory cell recruitment, leading to bone loss [ 3 ]. Cultured osteoblasts infected with bacteria secrete immune modulators of the inflammatory response, cytokines and chemokines, which trigger bone inflammation and destruction [ 65 , 101 , 102 ].…”
Section: Interaction Between S Aureus and Mg-6mentioning
confidence: 99%
“…After 2 h, cells were treated with ECNs or DPPC:POPG(7:3)/ECNs and incubated for 24 h, in a humidified environment (37 °C, 5% CO 2 ). At this time point, the effects of the two different experimental conditions on cell viability and cells proliferation were measured through the MTT method [ 63 , 64 ] and the Cell Proliferation Kit II (XTT), following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%